Graphical Product Quality and Muscle Activity in Children With Mild Disabilities Drawing on a Horizontally or Vertically Oriented Tablet. - Portnoy, Sigal; Mimouni-Bloch, Aviva; Rosenberg, Limor; Offek, Hagar; Berman, Tamar; Kochavi, Michal; Orman, Gal; Friedman, Jason (American Journal of Occupational Therapy)
OBJECTIVE. We compared performance level and muscle activity patterns during shape copying and tracing in two positions, while sitting at a desk and while standing in front of a wall, between typically developing (TD) preschool children and children with mild disabilities (MD). METHOD. Twenty-two TD children (8 boys, 14 girls; mean [M] age 5 5.2 yr, standard deviation [SD] 5 0.1) and 13 children with MD (9 boys, 4 girls; M age 5 4.9 yr, SD 5 0.5) participated in this study. RESULTS. The children performed faster and smoother movements when copying shapes on the vertical surface, with no reduction of accuracy, than on the horizontal surface. Children with MD exerted their upper trapezius while performing the short tasks on the vertical surface compared with their muscle activity on the horizontal surface. CONCLUSION. Incorporating short copying or drawing tasks on a vertical surface may increase the control of proximal muscles and ease graphomotor performance in children with MD.